Pismire Gully creates a waterfall near the Splink - Branch Cultural Historical Association (2009)
The Pismire Gully creates a waterfall on the cliff face close to the Splink. This gully was named for the abundance of ants (pismires) around its banks. Before it reaches the cliff face, the Pismire Gully provides convenient drinking water for livestock. Tracks in the winter snow and spring mud indicate this drinking spot is popular among wildlife such as rabbits, foxes and birds. The Pismire Gully and the Green Gulch gully flow year-round. Along the cliffs of the Wester Cove, other gullies create temporary waterfalls during spring runoff, refreshing sprays in summer, and frozen-in-time waterfalls in winter.